Valproate-induced Pedal Edema: Troublesome Side Effect yet Neglected? (Bangladesh Journal of Medical Science, 2024)
Valproate is a commonly used mood stabiliser that has various adverse effects. One such adverse effect is peripheral edema. This case report highlights a case of a 25-year-old female patient who presented with severe pedal edema after starting treatment with valproate for bipolar disorder. The patient had a few other risk factors for edema which makes the diagnosis challenging. Pedal edema is a troublesome adverse effect that can significantly impact the quality of life of patients taking valproate, yet it is often neglected. This case report emphasizes the importance of recognizing and managing valproateinduced peripheral edema in clinical practice.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 539-541